(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Effect of cadmium (Cd), chromium (Cr) and mercury (Hg) on liver histology of Clarias batrachus L. was studied after 28 days of exposure to sub lethal concentrations in the said metals under laboratory condition. The common changes in the liver were disruption of hepatic cords, abnormal shape of hepatocytes, pyknotic nuclei, and congestion of blood vessels and sinusoids. Cadmium induced frequent vacuolation in hepatocytes, loss of cell boundary, clumping of nuclei. Atrophied hepatocytes with variegated cytoplasm and necrosed nuclei were specific to Cr stress, and prominent intercellular spaces around most of the hypertrophied hepatocytes appeared in the liver under Hg stress. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13387 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):63-72, 2009